Warning line for preventing bone cement leakage in surgery involving percutaneous kyphoplasty for osteoporotic vertebral compression fractures - Li, Dongyue; Tao, Luming; Su, Qingjun; Zhang, Xinuo; Wu, Xingrui (Frontiers in Surgery, 2025)
BackgroundPercutaneous kyphoplasty (PKP) has achieved good clinical efficacy in the treatment of Osteoporotic vertebral compression fractures (OVCFs). However, how to reduce the bone cement leakage rate and improve safety during PKP surgery remains an urgent issue to be addressed in clinical practice. Therefore, the aim of this study was to identify a line, called the “warning line”, to determine whether there is leakage of bone cement during PKP surgery.MethodsFrom February 2018 to September 2022, 88 patients and 106 vertebral bodies with OVCFs treated with PKP by a single surgeon at our center were included in the study. Clinical general data were recorded. Vertebral bodies with bone cement reaching the apex of the posterior margin depression without leakage were designated Group A, whereas those with leakage were designated Group B. The posterior vertebral wall was divided into three equal parts in the postoperative three-dimensional CT scans, and the leakage rates at different positions of the posterior vertebral wall were analysed. In Group A without leakage, line b, called the warning line, was marked as the apex of cement diffusion.ResultsAll 88 patients successfully underwent surgery, with a significant decrease in the postoperative VAS score. No neurological complications occurred. Bone cement leakage rate was 58.5%. There were 44 vertebral bodies in Group A and 62 in Group B. No significant differences were found between the two groups in terms of age, bone density, balloon pressure, contrast dose, or cement volume (P > 0.05). The bone cement leakage rates in the upper third, middle third, and lower third of the posterior vertebral wall were 25%, 61.1%, and 66.7%, respectively, with statistically significant differences (P < 0.05). In Group A without leakage, the warning line was approximately 6.8% of the sagittal diameter from the posterior vertebral margin.ConclusionsPKP is a relatively safe treatment for OVCFs. Most bone cement leakage occurs in the middle and lower thirds of the posterior vertebral wall. When the apex of cement diffusion remains anterior to the warning line in PKP surgery, the posterior vertebral wall cement leakage rate is low.